STUDI ISLAM TENTANG AKHLAK KONSELOR - Hakim, Rosniati (Institut Agama Islam Negeri Imam Bonjol Padang, 2013)
Among the main characteristics of good Muslims, based on the Quran, is good behavior or conduct (akhlaq).Â It is a basic Islamic teaching that must be understood, internalized, and practiced in daily lives either personally or in society. It is said that akhlaq is like an endless sea.Â It cannot be separated with the other dimensions; it is in accord with thoughts, action and words, between commanding and keeping away of something.Â A Muslim counselor has to have Islamic conduct as reflected in Godâs characters, as well as character and conducts of Prophet Muhammad (peace be upon him).